2008
DOI: 10.1111/j.1746-1561.2008.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Directly Observed Physical Activity Levels in Preschool Children

Abstract: The study indicates that young children are physically inactive during most of their time in preschool. The preschool that a child attended was a stronger predictor of physical activity level than any other factor examined. Additional research is needed to identify the characteristics of preschools in which children are more active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
251
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(278 citation statements)
references
References 22 publications
19
251
3
5
Order By: Relevance
“…: not sedentary activity) was 50 (± 17) minutes during the period of preschool [10]. Boys had a higher percentage of MVPA, and 3.2% against 2.5% in girls, p=0.01 [5].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…: not sedentary activity) was 50 (± 17) minutes during the period of preschool [10]. Boys had a higher percentage of MVPA, and 3.2% against 2.5% in girls, p=0.01 [5].…”
Section: Resultsmentioning
confidence: 85%
“…Children spend an average of 22.5 to 30 hours per week in preschools [9,5], between 7.22 and 7.51 ± 1.14 horas hours [3,10,11] a day on average. Most of the time the children are inactive, predominantly SB, in all studies, with an MVPA around Week for 1 hour [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle behaviours such as physical and sedentary behaviour may well account for gender differences in elevated BP among children, researchers concluded that preschool-aged children (ECD) boys were more likely to engage in moderate-to-vigorous physical activity than girls, therefore we anticipate that boys should be more physically active compared to their counterparts girls [16], [33], [39], [44]. Gender differences in the elevated BP among children were influenced by several factors associated with age, weight, height and BMI in the children.…”
Section: Discussionmentioning
confidence: 99%
“…To enable inter-study comparisons, activity levels 1-2 were regarded as sedentary behaviour, activity level 3 as light physical activity and levels 4-5 as MVPA (Bower et al 2008;Nicaise, Kahan, and Sallis 2011;Pate et al 2008). Children's sedentary behaviour was described by the Activity-type code "Sitting, squatting, kneeling".…”
Section: Observation Of Physical Activity Children's Location and Somentioning
confidence: 99%